Necrotizing fasciitis post-acute appendicitis. - Fernandes, Cláudia (2011)
Necrotizing fasciitis (FN) is a deep infection of the subcutaneous tissue and fascia, resulting in its progressive destruction. Usually it evolves very quickly. The authors present a case to FN abdominal wall, an extremely rare complication of acute appendicitis. A child had surgical removal of the appendix because of gangrenous acute appendicitis, which evolved into severe infection, with pain and inflammatory process of the abdominal wall. After diagnosis, he underwent a surgical debridement of the abdominal wall and drainage of intraperitoneal abscess. Antibiotic therapy, surgical debridement and successive dressings were done and at 22nd day a dermo-epidermal graft was done in a small residual lesion of the abdominal wall. Because the prognosis is closely related to time to correct diagnosis and initiation of appropriate therapy, it's extremely important that this diagnosis is considered.